2005
DOI: 10.1111/j.1540-6288.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Asset Pricing and the Illiquidity Premium

Abstract: In this paper, we examine the asset-pricing role of liquidity (as proxied by share turnover) in the context of the Fama and French (1993) three-factor model. Our analysis employs monthly Australian data, covering the sample period from 1990 to 1998. The key finding of our research is that the main test is unable to reject the test of over-identifying restrictions, thus supporting the overall favorability of the liquidity-augmented Fama-French model. In addition, we find that the asset-pricing performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 50 publications
14
86
2
3
Order By: Relevance
“…The evidence for liquidity effect in international market was confirmed by Amihud et al [1997], Hu [1997], Chan and Fa [2005]. The issue of liquidity factor in the Polish market was examined by Lischewski and Voronkowa [2012] and Waszczuk [2013].…”
Section: Liquidity Factormentioning
confidence: 49%
“…The evidence for liquidity effect in international market was confirmed by Amihud et al [1997], Hu [1997], Chan and Fa [2005]. The issue of liquidity factor in the Polish market was examined by Lischewski and Voronkowa [2012] and Waszczuk [2013].…”
Section: Liquidity Factormentioning
confidence: 49%
“…Their results document that three-factor models outperform CAPM, and predicting returns on stocks traded on the Malaysian stock exchange can be slightly improved by incorporating illiquidity risk in a three-factor model. Chan and Faff (2003) examined the role of liquidity in asset pricing in the context of the Fama and French cross-sectional framework in an Australian setting. Hearn et al (2009) examined the role of company size and illiquidity in asset pricing in the context of the Fama and French cross-sectional framework in emerging African financial markets .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Carhart (1997) [4] introduced a Carhart 4-factor (C) model by augumenting the Fama-French 3-factor (FF3) model with momentum factor which can explain the short-term persistence in expected returns. Chan and Faff (2005) [5] advocated a liquidity-agumented FF3 model by using Australian data and find the liquidity factor is very robust to sensitivity checks. Connor, Hagmann and Linton (2012) [12] found that the profitability factor significantly improves the description of average return, and investment pattern in average returns is weak in China stock market.…”
Section: Introductionmentioning
confidence: 99%